Losses of female camel calves at different ages from birth to age at first calving* - BISSA, U K; YADAV, S B S; BENIWAL, B K; SAHANI, M S (The Indian Journal of Animal Sciences, 2014)
Postnatal losses in camel are more frequent than in other domesticated livestock species. In literature. calf losses have been noted in the range of 20-40%. The present study was undertaken to study the post calving losses of female calves from birth to age at first calving at ditTerent ages. The female calf mortality from birth to age at tirst calving (AFC) at different ages 0 to 3 month, 3 months to 1 year, 1 to 2 years, 2 to 3 years and 3 years to APC were 8.6, 3.3, 5.3,4.7 and 5%. total mortality was 21.89% before they reached the age at first calving. Period of birth have significant effect on mortality in 3 months to 1 year and 1 to 2 year-age group. Month of birth had significant effect on mortality at 0 to 3 months an.d 2 to 3 years. The culling offemale calves trom birth to APC at different ages 0 to 3 month, 3 months to 1 year. 1 to 2 years, 2 to 3 years and 3 years to AFC were observed as 0.18, 7.2, 11.9, 12.4 and 14.7% respectively. About 33% of the female calves born were culled due to different reasons congenital defects. deformities, poor wowth rate or late maturity etc, before they reached the breeding herd, Period of birth slgntficantly affect culling In 3 months to 1 year, 1 to 2 years and 2 to 3 years age group. The month of birth had highly significant effect only upon culling in 1 to 2 year age group.